IL-33 Mediated Inflammation in Chronic Respiratory Diseases—Understanding the Role of the Member of IL-1 Superfamily - Gabryelska, Agata; Kuna, Piotr; Antczak, Adam; Białasiewicz, Piotr; Panek, Michał (Frontiers in Immunology, 2019)
IInterleukin 33 (IL-33) is an alarmin cytokine from the IL-1 family. IL-33 is localized in the nucleus and acts there as a gene regulator. Following injury, stress or cell death it is released and exerts its pro-inflammatory biological functions via transmembrane form of the ST2 receptor, present mainly on immune cells. In recent years, IL-33 became a focus of many studies due to its possible role in inflammatory disorders. Among respiratory disorders, contribution of IL-33 to the development of asthma has been furthest identified. Increased level of IL-33 in lung epithelial cells and blood serum has been observed in asthma patients. The IL-33/ST2 interaction activated the Th2 mediated immune response and further production of many pro-inflammatory cytokines. Single nucleotide polymorphisms in IL-33 gene predispose to the development of asthma. Similarly, in chronic pulmonary obstructive disease (COPD), both increased expression of IL-33 and the ST2 receptor has been observed. Interestingly, cigarette smoke, a key inducer of COPD not only activates IL-33 production by epithelial and endothelial cells, but also induces the expression of IL-33 in peripheral blood mononuclear cells. Knowledge regarding its contribution in other respiratory disorders, such as obstructive sleep apnea, remains to be greatly limited. Recently it was shown that IL-33 is one of the inflammatory mediators that levels in blood serum are increased in OSA patients compared to healthy controls. This mini review summarizes current knowledge on IL-33 involvement in chosen chronic respiratory disorders and proposes this interleukin as a possible link in the pathogenesis of these diseases.